A facile access and evaluation of some novel thiazole and 1,3,4-thiadiazole derivatives incorporating thiazole moiety as potent anticancer agents - Gomha, Sobhi M. (Chem Cent J, 2017)
BACKGROUND: Many heterocyclic compounds containing thiazole or 1,3,4-thiadiazole ring in their skeletons have been reported to possess various pharmacological activities especially anticancer activities. RESULTS: 4-Methyl-2-phenylthiazole-5-carbohydrazide (2) was used as a synthon to prepare 2-(4-methyl-2-phenylthiazole-5-carbonyl)-N-phenylhydrazinecarbothioamide (3) and 2-(2-(4-methyl-2-phenylthiazole-5-carbonyl)hydrazono)-N′-phenylpropane hydrazonoyl chlorides 5a–c. In addition, thioamide 3 was used as starting material for preparation of a new series of thiadiazole derivatives via its reaction with hydrazonoyl chlorides 5a–c in dioxane using triethylamines as catalyst. In addition, a series of thiazole derivatives was synthesized by reaction of thioamide 3 with a number of α-halo compounds, namely, 3-chloropentane-2,4-dione (8) or 2-chloro-3-oxo-N-phenyl butanamide (10) phenacyl bromide 12 ethyl chloroacetate (14) in EtOH in the presence of triethylamine. The structures assigned for all the new products were elucidated based on both elemental analyses and spectral data and the mechanisms of their formation was also discussed. Moreover, the new products was evaluated in vitro by MTT assays for their anticancer activity against cell lines of Hepatocellular carcinoma cell line (HepG-2). The best result observed for compounds 7b (IC(50) = 1.61 ± 1.92 (μg/mL)) and 11 (IC(50) = 1.98 ± 1.22 (μg/mL)). The structure–activity relationships have been suggested based on their anticancer results. CONCLUSIONS: A novel series of new pharmacophores containing thiazole moiety have been synthesized using a facile and convenient methods and evaluated as potent anticancer agents. [Image: see text]